Future Directions for the Zygon Center - Barbour, Ian G. (Zygon, 2004)
Abstract. A brief comparison of the Zygon Center for Religion and Science and the Center for Theology and the Natural Sciences is given. The work and emphases of the two Centers overlap but also differ in significant ways. Without neglecting the physical sciences or the Christian tradition, ZCRS would do well to continue to give high priority to the biological sciences and the dialogue with the major world religions.